Cognitive Behavioral Therapy (CBH-I) untuk Insomnia pada Family Caregiver Pasien Kanker - Nurlelasari Harahap; Agung Waluyo (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of Cognitive Behavioral Therapy (CBT) in overcoming insomnia in family caregivers of cancer patients to improve their physical and psychological health and well-being. The method used is a non-systematic literature review, which discusses Cognitive Behavioral Therapy (CBT) in FCs who experience insomnia. The databases used are Sciencedirect, Proquest, Scopus, and google scholar. The results showed that of the seven articles reviewed, CBT-I interventions were an evidence-based solution that was not only safe and effective for the treatment of insomnia but also had the potential to improve the long-term health and well-being of FCs treating cancer patients. In conclusion, CBT-I is an effective and long-lasting treatment for chronic insomnia disorder with minimal cost, but so far, the evidence for the effectiveness of CBT has not changed practice; this is possible because the obstacles to the management of CBT-I still need to be resolved. Keywords: Cognitive Behavioral Therapy (CBT), Family Caregiver, Insomnia, Cancer